Bolivia : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bolivia. (IMF Staff Country Reports; Country Report ;, 2007)
Bolivia's 2007 Article IV Consultation reports that reforms are needed to make the budget a more effective developmental and poverty-reducing tool. The fiscal position has shifted into a substantial surplus, and public debt has been substantially reduced. Financial sector stability has improved, although dollarization is still high. Efforts to address remaining financial sector vulnerabilities should be intensified. Priority areas of reform include the adoption of prudential regulations to mitigate market risk and credit risks from dollarization; and of legislation governing corporate bankruptcy/restructuring.